KONTRIBUSI PERAN KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU SMK SE-KECAMATAN BAWANG KABUPATEN BATANG - Subagyono; Nurkolis; Yovitha Yuliejantiningsih (STKIP Subang, 2023)
The purpose of this research is to (1) Describe and analyze the contribution of the role of school principals to the performance of vocational school teachers in Bawang District, Batang Regency. (2) Describe and analyze the contribution of school culture to the performance of vocational school teachers in Bawang District, Batang Regency. (3) Describe and analyze the contribution of the role of the principal and school culture to the performance of vocational school teachers in Bawang District, Batang Regency, and prove the contribution of larger variables. The population in this study was all vocational school teachers in Bawang District, Batang Regency, totaling 66 people. The sample was 56 people using proportional random sampling technique. The data collection method used is the questionnaire method. Data analysis uses descriptive analysis, requirements testing, and hypothesis testing. To analyze the data using the SPSS 22.0 for Microsoft Windows program facilities. The research results show that (1) There is a partial positive and significant contribution from the role of school principals to the performance of vocational school teachers in Bawang District, Batang Regency, with a correlation value of 0.761 or 43.98% and a p-value <0.05. (2) There is a partial positive and significant contribution of school culture to the performance of vocational school teachers in Bawang District, Batang Regency, with a correlation value of 0.640 or 16.92% and a p-value <0.05. (3) There is a positive and significant contribution of the role of the principal and school culture simultaneously to the performance of vocational school teachers in Bawang District, Batang Regency, with a correlation value of 0.789 or 60.90% and a p-value <0.05. The advice that can be conveyed is that the Principal should always provide an understanding of all school components so that they always maintain traditions, school values which are the characteristics of the school and strengthen positive school culture, but what is more important is a culture of continuously improving the quality of the school.